Unveiling Tetraselmis subcordiformis lipidome dynamics during large-scale cultivation in open raceway pond - Imen Saadaoui (14159025) (2024)
A local microalgal strain of Tetraselmis subcordiformis was cultivated at large-scale using open raceway pond. The temporal influence on the growth and lipidomic profile of the strain was investigated using optic density (OD) measurement and ultra-high pressure liquid chromatography. Results showed that triglycerides represented 57% of the total lipids on day 11 (exponential phase) and stayed consistently high until stationary phase, without affecting the biomass quantity. Moreover, a high expression of monounsaturated fatty acids and polyunsaturated fatty acids such as ω-3 eicosapentaenoic acid (20:5), docosahexaenoic acid (22:6), palmitic (16:0) and palmitoleic acid (16:1) was observed by stationary phase. Carotenoid analysis also revealed the increase in lutein (65.2%) and β-carotene (71.4%) from day 6 to day 15. Our study showed that T. subcordiformis contained the highest amounts of valuable lipids, fatty acids and pigments in the stationary phase, which started on day 15 of culture. Other Information Published in: Journal of Applied Phycology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10811-023-03166-x